2016
DOI: 10.1111/ejh.12818
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in hematological disorders and malignancies

Abstract: Commonly known for its critical role in calcium homeostasis and bone mineralization, more recently vitamin D has been implicated in hematological cancer pathogenesis and shows promise as an anti-cancer therapy. Serum levels of 25(OH)D 3 , the precursor to the active form of vitamin D, calcitriol, are frequently lower in patients with hematological disease compared to healthy individuals. This often correlates with worse disease outcome. Furthermore, diseased cells typically highly express the vitamin D recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 82 publications
(196 reference statements)
1
58
0
Order By: Relevance
“…With gradual recognition of the role of vitamin D deficiency in many diseases [ 4 ], the relationship between vitamin D and iron status has also begun to be explored [ 1 ]. It has been demonstrated that a deficit of vitamin D increases the risk of many hematological disorders and iron metabolism disturbances [ 26 , 44 ], which was visible, especially in adults with different illnesses [ 26 ]. One reason for this is the pro-inflammatory effects of a vitamin D deficit, which eventually leads to an increase in hepcidin production, via stimulation of pro-inflammatory cytokines [ 31 ] and activation of the JAK-STAT3 pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With gradual recognition of the role of vitamin D deficiency in many diseases [ 4 ], the relationship between vitamin D and iron status has also begun to be explored [ 1 ]. It has been demonstrated that a deficit of vitamin D increases the risk of many hematological disorders and iron metabolism disturbances [ 26 , 44 ], which was visible, especially in adults with different illnesses [ 26 ]. One reason for this is the pro-inflammatory effects of a vitamin D deficit, which eventually leads to an increase in hepcidin production, via stimulation of pro-inflammatory cytokines [ 31 ] and activation of the JAK-STAT3 pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a deficit of vitamin D increases the risk of many hematological disorders and iron metabolism disturbances [ 26 , 44 ], which was visible, especially in adults with different illnesses [ 26 ]. One reason for this is the pro-inflammatory effects of a vitamin D deficit, which eventually leads to an increase in hepcidin production, via stimulation of pro-inflammatory cytokines [ 31 ] and activation of the JAK-STAT3 pathway [ 44 ]. Sun et al [ 34 ] pointed out that vitamin D can also downregulate hepcidin transcription, although the mechanism by which this occurs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a conformational change so VDR can bind its retinoid X receptor (RXR) binding partner, and this heterodimer moves to the nucleus to promote or repress transcription of certain genes [12]. This pathway turns off activated T cells by decreasing inflammatory cytokine production and STAT phosphorylation [13–17]. We previously showed this to be the case in T-LGLL patient peripheral blood mononuclear cells (PBMCs) in culture and in the TL-1 cell line, a model of T-LGLL [5, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency was also associated with a decrease in total survival and/or PFS for acute myeloid leukemia, CLL and NHL (24)(25)(26). In a study with 34,763 women with a median age of 63 years, moderate calcium replacement was shown to prevent lymphoid malignancies in elderly women (27). In our patient group, we could not find a relationship between complications, such as thrombosis, haemorrhage, erythrocytosis, thrombocytosis, leukocytosis, and vitamin D deficiency, but the number of patients was insufficient to make a solid conclusion.…”
Section: Discussionmentioning
confidence: 99%